Sclerosing mucoepidermoid carcinoma of salivary glands - Othman, Bacem Khalele; Bradová, Martina; Simpson, Roderick H. W.; Laco, Jan; Agaimy, Abbas; Rito, Miguel; Ihrler, Stephan; Steiner, Petr; Grossmann, Petr; Hájková, Veronika; de Rezende, Gisele; Goma, Montse; et al. (Springer Science and Business Media LLC, 2025)
Sclerosing mucoepidermoid carcinoma (SMEC) of the salivary glands is a rare variant of low-grade mucoepidermoid carcinoma with scanty cellular atypia characterized by marked fibrosis/sclerosis and a rich inflammatory infiltrate. Herein, we report 25 unpublished cases of SMEC, two of them with prominent eosinophilia (2/25; 8%) and three with abundant IgG4-positive plasma cells (3/25; 12%). In our series of salivary SMEC, molecular analysis using fluorescence in situ hybridization (FISH) and/or next-generation sequencing (NGS) provided evidence of MAML2 gene rearrangement in 18 cases of the 21 analyzable cases tested (86%), while this gene locus was intact in 3 cases (14%). This study focuses on the diagnostic criteria of salivary SMEC given its challenge of abundant collagenous stroma, minimal residual neoplastic areas, and inconspicuous mucous cells. Follow-up data of our cases indicate that salivary SMECs have favorable outcomes. Molecular analysis for MAML2 gene rearrangement suggests that SMECs of salivary glands represent a rare variant of conventional low-grade MECs of salivary glands. In contrast, SMECs of the thyroid gland are genetically distinct from salivary-type thyroid MECs.